Structure–function analyses of the G729R 2-oxoadipate dehydrogenase genetic variant associated with a disorder of l-lysine metabolism - Zhang, Xu (J Biol Chem, 2020)
2-Oxoadipate dehydrogenase (E1a, also known as DHTKD1, dehydrogenase E1, and transketolase domain-containing protein 1) is a thiamin diphosphate-dependent enzyme and part of the 2-oxoadipate dehydrogenase complex (OADHc) in l-lysine catabolism. Genetic findings have linked mutations in the DHTKD1 gene to several metabolic disorders. These include α-aminoadipic and α-ketoadipic aciduria (AMOXAD), a rare disorder of l-lysine, l-hydroxylysine, and l-tryptophan catabolism, associated with clinical presentations such as developmental delay, mild-to-severe intellectual disability, ataxia, epilepsy, and behavioral disorders that cannot currently be managed by available treatments. A heterozygous missense mutation, c.2185G→A (p.G729R), in DHTKD1 has been identified in most AMOXAD cases. Here, we report that the G729R E1a variant when assembled into OADHc in vitro displays a 50-fold decrease in catalytic efficiency for NADH production and a significantly reduced rate of glutaryl-CoA production by dihydrolipoamide succinyl-transferase (E2o). However, the G729R E1a substitution did not affect any of the three side-reactions associated solely with G729R E1a, prompting us to determine the structure–function effects of this mutation. A multipronged systematic analysis of the reaction rates in the OADHc pathway, supplemented with results from chemical cross-linking and hydrogen–deuterium exchange MS, revealed that the c.2185G→A DHTKD1 mutation affects E1a–E2o assembly, leading to impaired channeling of OADHc intermediates. Cross-linking between the C-terminal region of both E1a and G729R E1a with the E2o lipoyl and core domains suggested that correct positioning of the C-terminal E1a region is essential for the intermediate channeling. These findings may inform the development of interventions to counter the effects of pathogenic DHTKD1 mutations.